Discordant segregation of Xq28 markers and a mutation in the L1 gene in a family with X linked hydrocephalus. Issue 3 (March 1996) - Jouet, M; Strain, L; Bonthron, D; Kenwrick, S
Abstract : X linked recessive hydrocephalus is the most common hereditary form of hydrocephalus. Genetic analysis indicates that the majority of cases are caused by mutations in a single gene in Xq28, recently identified as the gene for neural cell adhesion molecule L1. Genetic heterogeneity for this disorder was suggested following the description of a single large pedigree where X linked hydrocephalus showed lack of linkage to Xq28 markers flanking the L1 gene. Mutation analysis in this family shows a single base pair deletion within the coding sequence of the L1 gene that would result in truncation of the mature protein. The nature of the mutation and its segregation with the disease through the pedigree indicate that it is the cause of X linked hydrocephalus in this family. These results are at odds with data obtained through segregation of alleles for markers flanking the L1 gene. Somatic and germline mosaicism is the most plausible explanation for these data, which also provide further evidence for genetic homogeneity of X linked hydrocephalus.